2017
DOI: 10.1039/c7py00736a
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired thermoresponsive polymers with a tunable LCST by Cu(0)-LRP for the construction of smart TiO2 nanocomposites

Abstract: Thermoresponsive polymers with different microstructures, a tunable LCST and terminal catechol anchors were synthesized by Cu(0)-LRP for the surface functionalization of TiO2 nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Such a kinetic behavior is consistent with a constant concentration of active species throughout the entire reaction, the absence of major side reactions, and consequently a well-controlled radical polymerization. Based on the successful synthesis of telechelic homopolymers, a random copolymerization of both monomers ([DEGA] 0 /[OEGA] 0 /[DI A/L ] 0 /[Me 6 -TREN] 0 = 40/7/1/0.2) was performed under similar conditions, aiming at building up a nontoxic thermoresponsive copolymer ATP3 with LCST close to body temperature. The random copolymerization reached 90% after 2 h, as proven by 1 H NMR spectroscopy, and GPC analysis confirmed the presence of a monomodal copolymer distribution with M n GPC = 12.1 kDa and M w / M n = 1.23 (Table ). As expected, the 1 H NMR spectrum of ATP3 in CDCl 3 (Figure S3, lower spectrum), a good solvent for both the core unit and copolymer chains, showed characteristic peaks associated with the repeating unit structure, i.e., δ 13,18 = 4.2 ppm, and middle-chain initiator residue, i.e., δ 9,7 = 6.7 and 5.4 ppm.…”
Section: Resultsmentioning
confidence: 96%
“…Such a kinetic behavior is consistent with a constant concentration of active species throughout the entire reaction, the absence of major side reactions, and consequently a well-controlled radical polymerization. Based on the successful synthesis of telechelic homopolymers, a random copolymerization of both monomers ([DEGA] 0 /[OEGA] 0 /[DI A/L ] 0 /[Me 6 -TREN] 0 = 40/7/1/0.2) was performed under similar conditions, aiming at building up a nontoxic thermoresponsive copolymer ATP3 with LCST close to body temperature. The random copolymerization reached 90% after 2 h, as proven by 1 H NMR spectroscopy, and GPC analysis confirmed the presence of a monomodal copolymer distribution with M n GPC = 12.1 kDa and M w / M n = 1.23 (Table ). As expected, the 1 H NMR spectrum of ATP3 in CDCl 3 (Figure S3, lower spectrum), a good solvent for both the core unit and copolymer chains, showed characteristic peaks associated with the repeating unit structure, i.e., δ 13,18 = 4.2 ppm, and middle-chain initiator residue, i.e., δ 9,7 = 6.7 and 5.4 ppm.…”
Section: Resultsmentioning
confidence: 96%
“…Herein Cu(0)-LRP was utilized for the synthesis of thermoresponsive polymer with terminal catechol anchor, which has shown well control over the molecular weight (MW) and MW distribution during the polymerization from unprotected dopamine-functionalized initiator (2bromo-N-(3,4-dihydro-xyphenethy)-2-methylpropanamide, DOPA-Br). 44,45 As shown in Scheme 1, GA was used as a co-monomer for the DOPA-Br-initiated copolymerization with NIPAM.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous report, a "one-pot" strategy has been used for simultaneous polymerization and post modification in order to avoid the multi-step purification procedures. 45 It is hypothesized that this strategy may help to reduce the side reactions between the epoxy ring and catechol groups, mostly due to the high reactivity of catechol groups toward TiO2. Thus TiO2 nanoparticles were directly added into the system at the beginning of the reaction for one polymerization conducted showed that a conversion of 93% could be obtained after two hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, stable SAMs can only be obtained on certain substrates where the interaction between catechol and surface is strong enough for achieving a proper stabilization of the molecular monolayer. This is the case of some metal oxides, where a coordination bond is established [32,33,34]. If only weak interactions come into play, such as hydrogen bonding, electrostatic forces or π–π stacking, cooperativity between catechol moieties is essential for generating a stable thin film on the surface.…”
Section: Introductionmentioning
confidence: 99%